Capitalisme agraire en Indonésie : les marchés du travail et de la terre comme déterminants des rapports salariaux dans les plantations de palmier à huile - Stéphanie Barral (Revue de la Régulation)
From globalization stems a rapid growth of agrarian capitalism. Large plantations are an emblem of this form of agricultural production inherited from the colonial times. They are subject to increasing political interest in several countries of the tropics. Development of oil palm plantations for instance have been supported by the government in Indonesia since the 1970s. This article questions the expansion of these plantations and the stabilisation of workers through the analysis of labor relations. A field study held in six large private plantations shows that the liberal and paternalist form of the welfare State leads to a strong influence of labor market on companies’ remuneration and protection policies. The study of workers’ individual economic initiatives also reveals land market as a decisive factor. In pioneer fronts were new private plantations have been settled since the 1980s, access to land ownership is a second parameter that shapes labor relations. The role of companies in the definition of social protections as well as access to land for complementary ones entails important geographic inequalities between agricultural laborers.